MENINGKATKAN KEMAMPUAN BERHITUNG MELALUI MEDIA DADU GEOMETRI PADA ANAK KELOMPOK A - Dwi Rosyidatul Kholidah (CENDEKIA, 2019)
Children are individual figures who are undergoing a process of very rapid development for life and organization which is a physical and spiritual unity that is intact with all its biological and psychological structures and devices so that it becomes a unique figure. Children experience a fundamental development process which means that development experiences at an early age can have a strong and long-term effect so that they underlie the child's subsequent developmental processes. Every child has a number of potential, both physical, biological, cognitive, and social emotional potential. The design of this study uses class action research (Classroom Action Research) with two cycles, where each cycle consists of four stages: planning, implementation, observation and reflection, while the instrument uses observation and documentation. The subjects of this study were 25 children of Group A in Mentari Harapan Blimbing Paciran Lamongan in the Academic Year of 2017/2018. Data analysis was carried out by means of descriptive qualitative with 65% individual completeness and 85% grade completeness. In this section, it can be concluded that, media playing geometry dice can improve numeracy skills in children in group A Mentari Harapan Blimbing Paciran Lamongan Academic Year 2017/2018, this is evident from the results of the pre-survey research with grade completeness reaching 59.2%, at Cycle I completeness grade 72% and in Cycle II completeness reaches 88.4%.